Perloff's Clinical Recognition of Congenital Heart Disease - Marelli, Ariane; Aboulhosn, Jamil (Elsevier, 2022)
Covering the full spectrum of CHD from infants through adults, Perloff's Clinical Recognition of Congenital Heart Disease, 7th Edition, provides unparalleled guidance on the diagnosis and treatment of common and uncommon CHD in one definitive resource.The editors of this new edition, Drs.Ariane J.Marelli and Jamil A.